Transforming Qur’anic Interpretation: Implications for Contemporary Islamic Education Management - Gusti Nur Alisah; Mujahidah Nurizzati; Leli Sartika; Hengki Satrisno; Bambang Irawan (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to analyze the transformation of Qur’anic interpretation from classical tafsir traditions to contemporary interpretive approaches and to examine its implications for strengthening Islamic education management. Social, cultural, and institutional changes increasingly require Islamic educational institutions to manage education in an adaptive manner while maintaining fidelity to the normative foundations of the Qur’an. This research employs a qualitative approach through library-based study, supported by thematic analysis of classical exegetical literature, contemporary hermeneutical studies, and recent scholarly works in the field of Islamic education management. The findings indicate that shifts in Qur’anic interpretive methodologies exert a significant influence on curriculum development, instructional strategies, leadership decision-making, and quality assurance systems within Islamic education. Thematic and contextual approaches to Qur’anic interpretation enable a more systematic integration of Qur’anic values with the demands of modern education. This study concludes that the transformation of Qur’anic interpretation plays a strategic role in constructing Islamic education management that is relevant, sustainable, and responsive to contemporary challenges.